AAV-Anti-miR-214 Prevents Collapse of the Femoral Head in Osteonecrosis by Regulating Osteoblast and Osteoclast Activities - Cheng Wang; Weijia Sun; Shukuan Ling; Yu Wang; Xin Wang; Haoye Meng; Yuheng Li; Xueling Yuan; Jianwei Li; Ruoxi Liu; Dingsheng Zhao; Qiang Lu; et al. (Elsevier, 2019)
Osteonecrosis of the femoral head, an intractable but common disease that eventually triggers collapse of the femoral head, is characterized by increased osteoclast activity and markedly decreased osteoblast activity in the necrotic region of the femoral head. MicroRNA (miRNA)-214 (miR-214) may play important roles in vertebrate skeletal development by inhibiting osteoblast function by targeting activating transcription factor 4 (ATF4) and promoting osteoclast function via phosphatase and tensin homolog (PTEN). This study revealed significantly increased levels of miR-214 in necrotic regions, with commensurate changes in the numbers of its target cells (both osteoblasts and osteoclasts). To investigate whether targeting miR-214 could prevent femoral head collapse, we constructed an adeno-associated virus (AAV)-associated anti-miR-214 (AAV-anti-miR-214) and evaluated its function in vivo. AAV-anti-miR-214 promoted osteoblast activity and diminished osteoclast activity, effectively preventing collapse of the femoral head in a rat model of osteonecrosis. Keywords: miRNA-214, osteonecrosis of the femoral head, osteoblast activity, osteoclast activity